Perancangan Strategi Sustainable Development Berbasis Co-Opetition antara Sektor UMKM Produk Hasil Laut dan Wisata Pantai Kenjeran Surabaya Guna Menciptakan Potensi Ecology Industrial Parks (EIP) - Astria Hindratmo; Nurwahyudi Widhiyanta (Journal of Research and Technology, 2020)
The Kenjeran area in Surabaya is a potential area that become a leading area because of coastal tourism and marine products processing MSMEs, so it is necessary to collaborate between MSMEs and tourism to achieve a continuous development. In addition, there is a need for the preservation of marine conditions around Kenjeran beach because of fish as the main raw material for MSMEs. There were three components to achieve sustainable development including MSMEs, coastal tourism, and the environment. They were expected to form an Ecology Industrial Parks (EIP) area for MSMEs by cooperating these three components. The purpose of this research was to design a sustainable development strategy based on co-opetition between MSMEs and coastal tourism to develop the area into EIP that considered the environmental sustainability. The methods used were IFE and EFE, SWOT, IE matrix and QSPM strategy selection. The results of this study were IFE produced a weighted score of 3.154 and EFE produced a weighted score of 3.118. SWOT analysis by using the TOWS matrix resulted a total of 44 strategies with 16 SO, 12 WO, 8 ST, and 8 WT strategies. The IE matrix results were in the position of cell I, resulting in 4 strategic categories namely forward and backward integration, market penetration, market development, product development. The QSPM results obtained the largest TAS, namely 7,133 in product development strategies.